Enhancing passive automation performance using an acoustic propagation simulation - Llorens, Ashley J.; Philip, Trudy L.; Schurman, Iman W.; Lorenz, Cory R. (Journal of the Acoustical Society of America, 2009)
During an at‐sea encounter, signatures of interest can exhibit characteristics that differ from those observed in previously recorded data. These differences can occur due to variations in a number of factors including encounter geometry, propagation channel, and receiving sensor configuration. This paper presents a simulation technique that imposes low‐frequency propagation effects on a time‐domain signal using a normal mode method. High‐quality, time‐varying recorded signatures are used as inputs into the algorithm, which outputs band‐limited time‐series data for a selected geometry and environment. The output time‐series are phased to simulate the time‐varying pressure amplitudes that would be received by a towed array or any multielement passive sensor configuration operating in a realistic multipath environment. These capabilities enable the simulation of signatures of interest as captured under a broad range of littoral conditions by various passive sensors. These simulated data are used to augment scarce signature collections for training and assessing the performance of passive sonar automation.